Application of JONSWAP Method for Analyzing Wave Height and Period on the Coastal of Poso, Tomini Bay, Poso Regency - David Bangguna; Irnovia B. Pakpahan; Ebelhart O. Pandoyu; Henny Indriyani Abulebu; Elce Misba Bansambua; Rahman Lamusu (Potensi: Jurnal Sipil Politeknik, 2025)
Poso Regency has great potential to be developed into a marine tourism and fisheries city due to its 64.6 km coastline, extending from Tumora in North Poso Pesisir District to Malei in Lage District. For the development of a marine tourism and fisheries city in Poso Regency, data related to wave height and period are required. One method for measuring wave height and period in a body of water is the JONSWAP (Joint North Sea Wave Project) method, an advancement of the Pierson-Moskowitz (1964) method. The JONSWAP method incorporates fetch length and wind speed parameters for calculating wave height and period, whereas other methods only use fetch length. This study aims to analyze wave height and period in Tomini Bay, using the JONSWAP method. The results show that the wind direction dominantly from the north, with most wind speeds (67.71%) being below 0.5 m/s. Wind gusts from the southeast were not detected on the wind rose because the area is located in the Verbeek Mountains; thus, southeast winds can be deflected. The average wind speed is 1.533 m/s, the significant wave height is 0.09 m, the peak wave period is 3.603 seconds, and the wave type is non-fully developed sea.